A Malware Detection Approach Based on Feature Engineering and Behavior Analysis - Manuel Torres; Rafael Alvarez; Miguel Cazorla (IEEE Access, 2023)
Cybercriminals are constantly developing new techniques to circumvent the security measures implemented by experts and researchers, so malware is able to evolve very rapidly. In addition, detecting malware across multiple systems is a challenging problem because each computing environment has its own unique characteristics. Traditional techniques, such as signature-based malware detection, have become less effective and have largely been replaced by more modern approaches, including machine learning and robust cross-platform behavior-based threat detection. Researchers employ these techniques across a variety of data sources, including network traffic, binaries, and behavioral data, to extract relevant features and feed them to models for accurate prediction. The aim of this research is to provide a novel dataset comprised of a substantial number of high-quality samples based on software behavior. Due to the lack of a standard representational format for malware behavior in current research, we also present an innovative method for representing malware behavior by converting API calls into 2D images, which builds on previous work. Additionally, we propose and describe the implementation of a new machine learning model based on binary classification (malware or benign software) using the previously mentioned novel dataset as its data source, thereby establishing an evaluation baseline. We have conducted extensive experimentation, validating the proposed model with both our novel dataset and real-world data. In terms of metrics, our proposed model outperforms a well-known model that is also based on behavior analysis and has a similar architecture.